Immunohistochemical Characterization of Hepatic Nuclear Factor 4 Alpha Expression in the Choroid Plexus of the lateral and 4th ventricles of adult Male Rat Brain - Rasha A. Salman; Taghreed Abdulrsool Ali; Duaa AL Musawi (Indian Journal of Forensic Medicine & Toxicology, 2022)
The choroid plexus (CP) is present in brain ventricles. It is responsible for cerebrospinal fluid (CSF) secretion and various vital functions. Special proteins present in choroidal epithelium play important roles in CSF production and energy metabolism.This study aims to compare between the lateral and fourth ventricles CPs using hepatocyte nuclear factor 4 alpha (HNF4α), metabolism marker, to evaluate the functional activity of this tissue in the two regions.Ten adult male albino rats were used to study the histological features of the CPs and to study the functional activity by quantitative immunohistochemical labeling with HNF4α marker.The CP of the fourth ventricle had more functional activity than the CP of the lateral ventricle. A quantitative assessment of HNF4α using Aperio ImageScope Software Analysis showed that the lateral ventricle CP mean positivity 0.264 ± 0.083 pixel/micron² while the fourth ventricle CP have mean positivity 0.297 ± 0.043 pixel/micron². The immunohistochemical expression of marker in the fourth ventricle CP were significantly, P ≤ 0.05 higher than those in the lateral ventricle at P ≤ 0.05. Immunohistochemical detection of metabolism marker went along with findings of other histological and biochemical studies to define the CP as a highly dynamic structure with regional variations forming a continuum of one entity tissue capable of functional adaptation according to body needs.